Assessing the efficacy of different semen extenders on post-thaw quality of Bangladeshi buffalo sperm under a manual cryopreservation protocol - Md. Ahsanul Kabir; S. M. Jahangir Hossain; Gautam Kumar Deb; Shahanaj Ferdousi Shejuty; Dipa Das; Abdullah Al Noman (Journal of Advanced Biotechnology and Experimental Therapeutics, 2024)
Cryopreservation has been used extensively for cattle in Bangladesh, albeit no study was conducted on the cryopreservation of buffalo sperm in Bangladesh. This study aimed to evaluate the suitability of different semen extenders for improving the post-thaw quality of Bangladeshi buffalo sperm under a manual cryopreservation protocol. The manual cryopreservation protocol was compared and optimized with a commercial biofreezer protocol. Then, the efficacy of different diluters was evaluated using the optimized manual cryopreservation protocol. Meanwhile, the post-thaw sperm quality in terms of motility and morphology was evaluated by CASA during the optimization process. During manual cryopreservation, the first cooling from 37 °C to 5 °C was done in a BLRI-developed equilibration chamber and the second cooling from 5 °C to -120 °C in a Styrofoam box using liquid nitrogen vapor from different distances (0.5, 1.5, 1.6, 2 and 3 inches). Simultaneously, another batch of sperm was cryopreserved using a programmable freezer. The highest number of motile sperms (62.67±1.12; P [ J Adv Biotechnol Exp Ther 2024; 7(1.000): 83-94]